BDNF and the Antidepressant Effects of Ketamine and Propofol in Electroconvulsive Therapy: A Preliminary Study - Huang XB (Dove Medical Press, 2020)
Xing-Bing Huang, Xiong Huang, Hong-Bo He, Fang Mei, Bin Sun, Su-Miao Zhou, Su Yan, Wei Zheng, Yuping Ning The Affiliated Brain Hospital of Guangzhou Medical University (Guangzhou Huiai Hospital), Guangzhou, People’s Republic of ChinaCorrespondence: Yuping Ning; Wei Zheng 36 Mingxin Road, Liwan District, Guangzhou, People’s Republic of ChinaTel +86-13322214239; +86-13322214239Fax +86-20-81891391; +86-20-81778169Email ningjeny@126.com; zhengwei0702@163.comObjective: Ketamine and propofol have become increasingly popular in electroconvulsive therapy (ECT) anaesthesia. This study was conducted to examine whether changes in serum levels of brain-derived neurotrophic factor (BDNF) are associated with the antidepressant effects of ketofol, a combination of ketamine and propofol, in ECT for patients with treatment-resistant depression (TRD).Methods: Thirty patients with TRD (18– 65 years) were enrolled and underwent eight ECT sessions with ketamine (0.5 mg/kg) plus propofol (0.5 mg/kg) (ketofol). Symptom severity was monitored using the 17-item Hamilton Depression Rating Scale (HAMD-17) and the Brief Psychiatric Rating Scale (BPRS), and serum levels of BDNF were examined by enzyme-linked immunosorbent assay (ELISA) at baseline and after 2, 4, and 8 ECT treatments. Serum levels of BDNF were also collected from thirty healthy controls.Results: At baseline, there were no significant differences in serum levels of BDNF between patients with TRD and healthy controls. The response and remission rates in patients with TRD were 100% (30/30) and 53.3% (16/30) after ECT treatment, respectively. Despite a significant reduction in HAMD-17 and BPRS scores after ECT, no changes in serum levels of BDNF were observed after ECT treatment when compared to baseline. No association was found between serum levels of BDNF and changes in illness severity.Conclusion: Serum levels of BDNF did not represent a suitable candidate biomarker for determining the antidepressant effects of ketofol during ECT for patients with TRD.Keywords: BDNF, ketamine, propofol, electroconvulsive therapy, treatment-resistant depression